The impact of manager characteristics on fund performance in the US market: an empirical analysis based on equity funds - He, Jiazhe (2020)
Since the establishment of the first open-end fund "Massachusetts Investor Trust" in the US, mutual funds have become increasingly important in the US economy, reflected in the rapid growth in market size and the active participation of household investors. In the meantime, as a professionally managed investment method, managers directly determine the investment strategy, making the personal characteristics of the manager gain more and more attention. Therefore, this work emphasizes on the impact of managers' personal characteristics on fund performance. Based on the previous literature, we mainly select the characteristics from four aspects: physiological characteristics, educational background, professional skills, and work experience for research. In this way, we chose 348 open-end equity funds as our sample and employed the panel data during the period from January 2017 to December 2019. After conducting empirical analysis through the fixed effects model, we find that there are some significant differences between the characteristics of equity fund managers and fund performance. We have proved that the age, MBA degrees and the number of funds managed are significantly correlated with fund performance. Among them, there is a negative relationship between age and fund performance, and whether to have an MBA degree is positively related to fund managers. Meanwhile, managers who administer more funds tend to have higher fund performance. In addition, we also observe that there is no statistically significant correlation between the gender, CFA qualification, tenure and fund performance. Finally, this work also puts forward several policy recommendations for investors and fund management companies based on the research results.